Restoration of blinking reflex and facial symmetry in a Bell's palsy patient - Priyanka Somani; Ajay Kumar Nayak (Wolters Kluwer Medknow Publications, 2011)
Patients afflicted with Bell's palsy are faced with both functional and esthetic impairment. Prominent among these are the inability to close the eyelids and abnormal facial appearance, with concomitant difficulty in eating, drinking and speaking. Rehabilitation of such patients can be achieved by a multispecialty approach, with the prosthodontist functioning as an integral part of the treatment team. This article describes a simple and effective approach to restore the blinking reflex of the upper eyelid with custom gold implant and facial esthetics with cheek support prosthesis.